Backpages. (Contemporary Theatre Review, 2015)
Backpages is an opportunity for the academy to engage with theatre and performance practice with immediacy and insight and for theatre workers and performance artists to engage critically and reflectively on their work and the work of their peers. Featuring short, topical articles and debates, polemics where necessary, it’s a place of intellectual intervention and creative reflection. It’s also where we hope to articulate, perhaps for the first time, the work of new and rising theatre artists in an academic forum.